PHENOLOGICAL OBSERVATIONS IN INTRODUCED FORMS AND VARIETIES OF CHERRY PLUM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents the results of the phenological phases of cherry plum vegetationin the conditions of the Chui valley of Kyrgyzstan. Observations were carried out on 28 varietiesof cherry plum from the collection of the Botanical Garden. The results of the introduction of wildgrowing cherry plum and cultivars are presented.
Keywords: Phenology of observation vegetation phase, introduction, Sogdian cherry plum, cherry plum varieties, buds, flowers, fruits, biotic and abiotic environmental factors